2013
DOI: 10.5455/medarh.2013.67.111-114
|View full text |Cite
|
Sign up to set email alerts
|

OSA-18 Survey in Evaluation of Sleep-disordered Breathing in Children with Adenotonsillar Hypertrophy

Abstract: Adenoidectomy and adenotonsillectomy improve QOL in children with SDB, which is caused by adenotonsillar hypertrophy. The OSA-18 survey is a useful tool for the selection of children for surgery with SDB caused by adenotonsillar hypertrophy and to assess quality of life after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Prospective and retrospective studies included in this systematic review are summarized in Supplemental Table S1 (available in the online version of the article). 2,7-42 An itemized assessment of the risk of bias is presented in Table 1 . OSA-18 was by far the most common validated measure used to measure quality of life, while some studies used the Obstructive Sleep Disorders–6, the Child Health Questionnaire, and the PedsQL (Pediatric Quality of Life Inventory).…”
Section: Resultsmentioning
confidence: 99%
“…Prospective and retrospective studies included in this systematic review are summarized in Supplemental Table S1 (available in the online version of the article). 2,7-42 An itemized assessment of the risk of bias is presented in Table 1 . OSA-18 was by far the most common validated measure used to measure quality of life, while some studies used the Obstructive Sleep Disorders–6, the Child Health Questionnaire, and the PedsQL (Pediatric Quality of Life Inventory).…”
Section: Resultsmentioning
confidence: 99%
“…OSAS-18 is a validated instrument that assesses SDB-related quality of life and has became an important outcome measure in children with SDB [11,12]. Using the OSAS-18 survey, a significant improvement was found in HRQoL after T&A in children with SDB with and without NE.…”
Section: Discussionmentioning
confidence: 96%
“…11 OSA-18 has been shown to be effective as a tool to compare the quality of life before and after adenotonsillectomy. 15,16 However, some clinical researches suggested that OSA-18 had poor validity in detecting and predicting pediatric OSA. 17,18 The OSA-18 questionnaire consists of 18 items including psychological and parental parameters as well as physical parameters.…”
Section: Discussionmentioning
confidence: 99%